Adiponectin Levels Are Reduced While Markers of Systemic Inflammation and Aortic Remodelling Are Increased in Intrauterine Growth Restricted Mother-Child Couple. (22nd June 2014) - Visentin, Silvia; Lapolla, Annunziata; Londero, Ambrogio Pietro; Cosma, Chiara; Dalfrà, Mariagrazia; Camerin, Martina; Faggian, Diego; Plebani, Mario; Cosmi, Erich
Abstract : Aim of the Study . To investigate the relationships between the adipocytokine levels, markers of inflammation, and vascular remodelling in pregnancies complicated by intrauterine growth restriction (IUGR). Materials and Methods . This was a retrospective study. One hundred and forty pregnant patients were enrolled. Adiponectin, leptin, tumor necrosis factor α (TNF α ), interleukin-6 (IL-6), and C reactive protein (CRP) were assessed in IUGR, small for gestational age (SGA), and appropriate for gestational age (AGA) mother-child couples at delivery. IUGR and SGA fetuses were defined as fetuses whose estimated fetal weight (EFW) was below 10th percentile for gestational age with and without umbilical artery (UA) Doppler abnormalities, respectively. Fetal aorta intima media thickness (aIMT) was evaluated by ultrasound in the same fetal groups. Data were analyzed by R (version 2.15.2). Results . There were 37 IUGR mother-child couples, 33 SGA, and 70 AGA. Leptin, TNF α, IL-6, and CRP serum levels were higher in IUGR pregnant patients (P < 0.05 ). Adiponectin levels were significantly reduced in IUGR fetuses compared to SGA and AGA, while leptin, TNF α, and IL-6 levels were higher in IUGR group (P ≤ 0.05 ). Fetal aIMT was significantly higher in IUGR (P < 0.05 ) and in this group there was a negative correlation between aIMT and adiponectin/leptin ratio (A/L ratio) (P < 0.05 ) and between adiponectin and IL-6 levels (P < 0.05 ). Conclusions . In conclusion, compared to SGA and AGA, IUGR fetuses had reduced circulating levels of adiponectin and elevated measures of aIMT and several inflammatory markers. Moreover, adiponectin levels were negatively correlated with aIMT in IUGR fetuses suggesting a possible causal link between reduced adiponectin and vessel remodelling.